Aplicación de tres fungicidas en semillas de arroz inoculada con Rhizoctonia solani y Gaeumannomyces graminis - Urrutia Morante, Gilbert Jeampierre (2023)
The objective of this research was to evaluate the application of three fungicides on rice seeds inoculated with R. solani and G. graminis. The study was conducted at the Phytopathology Laboratory of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7.5 of the Babahoyo - Montalvo road, Los Ríos province. For the in vitro laboratory tests, rice planting material of the Ferón variety was used. For the sensitivity tests of phytopathogenic fungi to disinfectant fungicides, two inocula of phytopathogenic fungi R. solani and G. graminis were used; the experimental design was completely randomized in AXB factorial arrangement with 9 treatments and 4 replications, where factor A is the fungicide products and factor B the doses to be used. Comparisons of means were made with Tukey's test at 5% statistical significance. The following variables were evaluated: Growth variables: Radial growth rate, radial growth mean, radial growth rate, sensitivity of isolates to commercial fungicides and seed germination. From the results obtained it was determined that the fungicide Propiconazole at a dose of 700 ml/kg of seed significantly decreased the accumulated radial growth of G. graminis (3.40 mm) and R. solani (3.45 mm), the mean radial growth rate of G. graminis (1.70 mm) and R. solani (1.73 mm), the radial growth rate of G. graminis (0.00 mm.h-1) and R. solani (0.00 mm.h-1) and caused greater sensitivity on the phytopathogens G. graminis (95.89 %) and R. solani (95.83 %); as well as the fungicide treatment Carboxin - Thiram at a dose of 350 ml/kg of seed increased the germination period of rice seeds (6.75 days).